Please Don’t Look at Me That Way. An Empirical Study Into the Effects of Age-Based (Meta-)Stereotyping on Employability Enhancement Among Older Supermarket Workers - Peters, Pascale; Van der Heijden, Beatrice I. J. M.; Spurk, Daniel; De Vos, Ans; Klaassen, Renate (Frontiers in Psychology, 2019)
At present, individuals increasingly have to take ownership of their working lives. This situation demands that they anticipate on how to self-manage and plan their careers. However, individuals’ career management does not happen in a vacuum. Therefore, studies have stressed the importance of organizations introducing sustainable Human Resource Management to share the responsibility for individuals’ employability, which motivates them to work longer across the life-span. This may especially hold for disadvantaged workers, such as older workers (≥ 50 years) and those working in lower-skilled jobs. Witnessing the emerging scholarly and societal attention for Sustainable Career Development (SCD), this study examines the relationships between workers’ chronological age (comparing older workers with younger and middle-aged groups, respectively) and dimensions of self-reported employability, and how these are moderated by perceptions of negative (meta-)stereotyping regarding older workers’ productivity, reliability and personal adaptability. To examine how the psychological mechanisms underlying these relationships can affect individuals’ labor market decisions and behaviors, we developed a set of hypotheses building on socio-emotional selectivity and self-categorization theory, which we tested using data collected among supermarket workers in various age groups (N = 98). Moderated regression analyses showed that, in line with our hypotheses, perceptions of negative age-based (meta-)stereotyping amplifies the negative effect of older workers’ age on their self-perceived employability. In particular: 1) the older worker group reported lower levels of employability (i.e., anticipation and optimization, corporate sense, and balance) and 2) perceptions of stronger negative (meta-)stereotypes regarding older workers in the organization had a moderating effect on the relationship between age group and four of the five distinguished employability dimensions (i.e., occupational expertise, anticipation and optimization, corporate sense, and balance, but not personal flexibility). We conclude that both age and negative (meta-)stereotypes refrain older workers from enhancing their employability. This may potentially impact their career decisions and opportunities, especially in view of swift changing labor market demands. We argue, therefore, that Sustainable HR practices should contribute to opposing negative age-based (meta-)stereotyping and need to focus on creating an inclusive work climate, meanwhile paying attention to stimulating ambition among, and creating career opportunities for all workers across the life-span.